Tunable Schottky barrier in van der Waals heterojunction composed of graphene and SiCP4 from first principle calculations - Zhang, Shaofeng; Wang, Zhaowu (Results in physics, 2023)
•The Schottky contact formed between graphene and SiCP4 is studied.•The barrier height and contact type can be tuned by changing the interlayer distance.•The charge transfer theory can be used to explain the change of Schottky barrier.•The Schottky barrier can be controlled by applying a vertical electric field. The contact type between graphene and semiconducting two-dimensional materials is a crucial factor in determining the performance of nanoscale electronic devices based on two-dimensional materials. Recently, SiCP4 is proposed to have high charge mobility plus high stability. In this work, we study the contact type between graphene and SiCP4. The Schottky barrier is formed between graphene and SiCP4. By changing the interlayer distance, the Schottky barrier can be tuned in a wide range. The charge transfer at the interface induces a reverse shift between the bands of graphene and SiCP4. The amount of charge transfer can be used to explain the change in the Schottky barrier. Furthermore, the Schottky barrier can be controlled by applying a vertical electric field. The tunable Schottky barrier provides a guide for the design of the nanodevice based on graphene and SiCP4.